100 questions & answers about lung cancer - Schiller, J. H. (Joan H.), 1954- .); Cipau, Amy; Parles, Karen (Sudbury, Mass. : Jones and Bartlett Publishers, 2010)
Overview: EMPOWER YOURSELF! No one with lung cancer needs to be alone in their fight against this disease. 100 Questions & Answers About Lung Cancer, Second Edition, enables patients and their families to seek out the best treatment possible for early detection of lung cancer. Providing both the doctor's and patient's point of view, this book is a complete guide to understanding treatment options, post-treatment quality of life, sources of support, and much more. Through 100 Questions & Answers About Lung Cancer, Second Edition, expert authors use their experiences with patients to provide support and hope to the tens of thousands of people coping with lung cancer
Part 7: Side Effects Of Chemotherapy: -- Questions 70-79 describe the side effects that you encounter through chemotherapy treatments: -- What are the common side effects of chemotherapy? -- What are blood counts, and what should I know about them? -- Why am I always exhausted? What can I do for fatigue? Will the fatigue go away after my treatment is over? -- Part 8: Coping With Symptoms Of Lung Cancer: -- Questions 80-85 cover common symptoms, side effects and complications of lung cancer and its treatment: -- Can my shortness of breath be controlled? -- What can I do to relieve pain? -- Am I at risk for a blood clot? What is a pulmonary embolism? -- Part 9: Living With Lung Cancer: -- Questions 86-93 provide practical advice on lifestyle choices or changes that you may encounter following a lung cancer diagnosis: -- How should I change my diet following a lung cancer diagnosis? -- Can diet affect my survival from lung cancer? -- I I smoke, is there any reason to quit? -- Part 10: If Treatment Fails: -- Questions 94-97 address the difficult issues that arise if treatment options fail: -- How do I decide if it's time to stop treatment? -- What is hospice? -- What can I do to prepare for my death? -- Part 11: Prevention, Screening, And Advocacy: -- Questions 98-100 discuss a variety of options for prevention, ways to screen for lung cancer, and advocacy: -- Can lung cancer be prevented? What is cheoprevention? -- Is there a screening test for lung cancer? -- Why has there been so little progress is fighting lung cancer? What can I do to help? -- Appendix -- Glossary -- Index
Parles' name appears first on the earlier edition
Includes bibliographical references and index
13
Keywords: Lung Neoplasms -- Popular Works; Lungs -- Cancer -- Popular works